Challenges and Strategies for Productive Waqf Management: An Analysis of Muhammadiyah’s MPW and its Role in Community Economic Development - Mursal, Mursal; Salman Munthe; Rahmat Ilyas; Muhammad Farhan Abimayu (Sekolah Tinggi Agama islam Negeri Majene, 2025)
MPW is an institution established by Muhammadiyah to manage Waqf. Although its role in supporting the welfare of the community in Padang City, its actual economic impact requires further investigation, making it an interesting topic for research. This study aims to analyse the role of MPW in optimising productive Waqf to support the local economy. Using a qualitative case study approach, primary data was collected through in-depth interviews with regional executives and three Waqf beneficiaries. Secondary data was obtained from a review of relevant literature. The findings highlight several key points. With regard to the achievement of objectives, the economic impact on beneficiaries remains limited, and full economic independence has not yet been achieved. This requires a strategic shift from direct assistance towards empowerment through entrepreneurship training, small business mentoring, and results-based evaluation. In terms of integration, the low participation of beneficiaries in planning and evaluation, coupled with one-way communication, highlights the need for two-way communication forums, greater involvement of beneficiaries, and synergy with Islamic financial institutions to increase inclusiveness. Finally, in terms of adaptation, challenges in adjusting to local needs, ensuring transparency, and guaranteeing sustainability require solutions such as publishing open reports, developing programmes based on local needs, and involving relevant stakeholders.